J Surgical Endocrinol 2020
DOI: 10.36959/608/443
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and Clinicopthologic Properties of Patients Operated for Adrenal Masses

Abstract: Background:The prevalence of adrenal incidentaloma is nearly 4 to 10% and increases with age. Most adrenal masses are nonfunctioning adrenocortical adenomas and found as an adrenal incidentaloma in 80% of cases, but also be conditions requiring therapeutic intervention. We presented our patients with adrenal masses and their management. Patients and methods:We documented age and gender of patients, and also size, clinical and histopathologic diagnoses of the adrenal masses; diagnostic dilemmas and preferred op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(35 reference statements)
0
0
0
Order By: Relevance
“…The prevalence of adrenal cancer is approximately 4% to 10% and increases with age, with most adrenal glands showing no hormonal activity. However, when adrenal lesion hormonal activity is detected, it usually leads to a diagnosis of Cushing's syndrome, pheochromocytoma, or Conn's syndrome [2]. In a single center study, the prevalence of Conn syndrome was reported to be 2.6% of patients in primary care [3].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of adrenal cancer is approximately 4% to 10% and increases with age, with most adrenal glands showing no hormonal activity. However, when adrenal lesion hormonal activity is detected, it usually leads to a diagnosis of Cushing's syndrome, pheochromocytoma, or Conn's syndrome [2]. In a single center study, the prevalence of Conn syndrome was reported to be 2.6% of patients in primary care [3].…”
Section: Discussionmentioning
confidence: 99%